Assessing gas transit risks: Russia vs. the EU - Chloé Le Coq; Elena Paltseva (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2011)
This paper proposes a Transit Risk Index (TRI) designed to assess the riskiness of pipeline gas imports and to study the effect of introducing new gas routes. TRI controls for gas dependency, transit route diversification, political risks of transit, pipeline rupture probability, and the balance of power between supplying and consuming countries along the transit route. Evaluating TRI for the EU-Russia gas trade, we show that the introduction of the Nord Stream pipeline would further widen already large disparities in gas risk exposure across the EU Member States. The gas risk exposure of the Member States served by Nord Stream would decline. In contrast, EU countries not connected to Nord Stream, but sharing other Russian gas transit routes with the Nord Stream countries, would face greater gas risk exposure. We discuss the implications of our analysis for the design of the common energy policy in the EU.
Keywords: C80; Q40; Q48; 330; Gas transit risk; Index; Security of supply; Nord Stream; Common Energy Policy